2013
DOI: 10.1002/grl.50672
|View full text |Cite
|
Sign up to set email alerts
|

Controls on recent Alaskan lake changes identified from water isotopes and remote sensing

Abstract: [1] High-latitude lakes are important for terrestrial carbon dynamics and waterfowl habitat driving a need to better understand controls on lake area changes. To identify the existence and cause of recent lake area changes in the Yukon Flats, a region of discontinuous permafrost in north central Alaska, we evaluate remotely sensed imagery with lake water isotope compositions and hydroclimatic parameters. Isotope compositions indicate that mixtures of precipitation, river water, and groundwater source~95% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
95
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(100 citation statements)
references
References 38 publications
2
95
3
Order By: Relevance
“…3), we are unable to determine the relative contributions of these two lake water sources based on these data alone. Similarly, isotope analyses in Yukon Flats, Alaska, were unable to distinguish the influence of permafrost meltwater from snowmelt for a small group of lakes that plotted on a distinctly lower LEL compared to most other lakes sampled (Anderson et al, 2013). In contrast to other studies (e.g., Turner et al, 2010Turner et al, , 2014Tondu et al, 2013), we did not observe that lakes situated in catchments with high proportions of woodland/forest and tall shrub vegetation receive substantial snowmelt inputs.…”
Section: Development Of Isotope Frameworkcontrasting
confidence: 99%
See 1 more Smart Citation
“…3), we are unable to determine the relative contributions of these two lake water sources based on these data alone. Similarly, isotope analyses in Yukon Flats, Alaska, were unable to distinguish the influence of permafrost meltwater from snowmelt for a small group of lakes that plotted on a distinctly lower LEL compared to most other lakes sampled (Anderson et al, 2013). In contrast to other studies (e.g., Turner et al, 2010Turner et al, , 2014Tondu et al, 2013), we did not observe that lakes situated in catchments with high proportions of woodland/forest and tall shrub vegetation receive substantial snowmelt inputs.…”
Section: Development Of Isotope Frameworkcontrasting
confidence: 99%
“…Hydrological changes induced by climate change might have additional influence on limnological properties and biogeochemical cycling of these lakes, yet little is known about the hydrological processes that influence thermokarst lake water balance conditions in this region. Recent isotope-based studies from the western Hudson Bay Lowlands (Wolfe et al, 2011, Bouchard et al, 2013, Old Crow Flats (Tondu et al, 2013;Turner et al, 2010Turner et al, , 2014, Yukon Flats (Anderson et al, 2013) and northern Alberta (Gibson et al, 2015(Gibson et al, , 2016a concluded that shallow thermokarst lakes are hydrologically dynamic systems yielding a great diversity of lake water balance conditions, variably influenced by hydrological processes (snowmelt, rainfall, permafrost meltwater, evaporation) and catchment features (vegetation, topography; Table 1). The stable isotope mass balance approach has also been used to characterize the influence of hydrological processes on non-thermokarst northern lakes (Gibson and Reid, 2014;Gibson et al, 2015;Gibson et al, 2016b) and on lakes elsewhere (Steinman et al, 2013;Jones et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thawing changes hydraulic connections between different water pools (Carey and Woo, 2000), further affecting the groundwater flow path and its interaction with surface water (e.g., Bense and Person, 2008;Carey and Quinton, 2005;Woo et al, 2008;Zhang et al, 2013). For example, groundwater-surface water interactions in Alaska were more commonly found in areas of discontinuous permafrost where hydraulic connections were spatially and temporally variable (e.g., Anderson et al, 2013;Minsley et al, 2012;Walvoord et al, 2012). At high latitudes, permafrost distribution may affect lake density in addition to surface flow (Anderson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, groundwater-surface water interactions in Alaska were more commonly found in areas of discontinuous permafrost where hydraulic connections were spatially and temporally variable (e.g., Anderson et al, 2013;Minsley et al, 2012;Walvoord et al, 2012). At high latitudes, permafrost distribution may affect lake density in addition to surface flow (Anderson et al, 2013). In areas of continuous permafrost, subpermafrost groundwater is often isolated from the surface, and there are unique mechanisms in thermokarst lake dynamics such as lateral expansion and breaching (Jones et al, 2011;Plug et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation